E-049 Reduced supply cost for mechanical thrombectomy in large vessel occlusions with a bundling cost program for instrumentation. (23rd July 2022) - Catapano, J; Koester, S; Naik, A; Winkler, E; Srinivasan, V; Desai, S; Albuquerque, F; Ducruet, A; Jadhav, A
Abstract : Introduction: The societal and economic burdens of stroke are significant. Bundling cost programs have previously shown to be effective in reducing cost for stroke care. Our aim was to assess the efficacy of bundling costs for instruments used in mechanical thrombectomy at our single institution. Methods: A retrospective review of all patients who underwent a mechanical thrombectomy at a single comprehensive stroke center over a 5-month period from 11/1/21 to 3/26/22 was performed. All patients with cost bundling instrumentation were analyzed for cost of the procedure, as well as al carte cost without the bundling. An independent t-test was performed comparing the average cost. A p-value <0.05 was defined as significant. Results: A total of 26 patients were included in the analysis. The average total cost using a la cart purchasing was $192, 619 whereas bundling total cost was $173, 338, accounting for a total cost savings of $19, 281. The average a la carte cost per patient was significantly greater than the average bundle cost per patient ($7, 408 (sD 3474.97) vs $6, 667 (sD 3162.09), p = <0.0001). The average cost savings per patient was therefore $742 (sD 386.39, range = $70 - $1575). Conclusion: Purchasing devices used for stroke using a bundled model could result in significant cost savings to the hospital, potentially minimizing the annual health care costs of stroke while maintaining therapeutic efficacy. Future studies should assess the feasibility and effectiveness of bundling methods for acute ischemic stroke supplies to determine optimal pricing and reduce the financial burden of stroke on the healthcare and hospital system. Disclosures: J. Catapano: None. S. Koester: None. A. Naik: None. E. Winkler: None. V. Srinivasan: None. S. Desai: None. F. Albuquerque: None. A. Ducruet: None. A. Jadhav: None.